Influence of the cubic spectral phase of high-power laser pulses on their self-phase modulation. (February 2016) - Ginzburg, V.N.; Kochetkov, A.A.; Yakovlev, I.V.; Mironov, S.Yu.; Shaykin, A.A.; Khazanov, E.A.
Abstract: Spectral broadening of high-power transform-limited laser pulses under self-phase modulation in a medium with cubic nonlinearity is widely used to reduce pulse duration and to increase its power. It is shown that the cubic spectral phase of the initial pulse leads to a qualitatively different broadening of its spectrum: the spectrum has narrow peaks and broadening decreases. However, the use of chirped mirrors allows such pulses to be as effectively compressed as transform-limited pulses.